PENGOLAHAN BUAH TERUNG POKAK (Solanum torvum) MENJADI TEH HERBAL SEBAGAI MINUMAN FUNGSIONAL - Nunuk Helilusiatiningsih (Universitas Tribhuwana Tunggadewi, 2020)
Pokak growing in fertile highlands is still classified as a wild plant and contains good bioactive and nutritional compounds. Drinks made from pokak are potential health drinks. The problem of pokak is relatively little consumed by the people of Indonesia. The results of the pokak research indicate that there are polyphenol compounds, tannins, flavonoids, caffeine, fumaric acid, maleic acid, alkaloids, carbohydrates, proteins, fats, vitamins, minerals. The aims of this research to process pokak eggplant fruit into 2 types of herbal teas, namely black tea and pokak green tea. The observation parameters were the organoleptic test, chemical component test including bioactive compounds and nutrients. The research method used the Fridman test, phytochemical screening, proximate test, Vitamin C, and minerals. The best organoleptic test results include aroma, taste, color, the most preferred by consumers is code 862 TB, namely pokak black tea. Qualitatively, pokak black tea contains saponins, glucosides, steroids, alkaloids. The nutritional test contains carbohydrates, fat, protein, ash content, moisture content, vitamin C. contains minerals Ca, Mg, Fe. The results of the study prove that Pokak herbal tea has a function for health and is potential as a functional drink.